Análisis Técnico-Financiero de las operaciones de servicio a pozo en el Campo Velásquez con base a las estadísticas obtenidas en OpenWells (2018)
The following work is done for Velásquez Field. Initially the generalities and geology of the Field and the Middle Valley of Magdalena were described. Subsequently, a categorization and description of all the well services performed in it was carried out. After this, all the activities that the Mansarovar Energy Colombia Ltd. company develops in its Well Service operations were codified and adapted with respect to the way of working in the Velásquez Field. In addition, the failures of the database with which the reports of the different services to well were being carried out were described. To understand the applicability of the OpenWells software in the Well Service operation, it was necessary to generate representative statistics with respect to the reports made in the last 6 months, for which the Data Analyzer module and the Microsoft Excel Software were used. Finally, a financial evaluation was carried out where two situations were studied, the first before adapting and implementing the OpenWells software and the second after starting the aforementioned software. All this to perform a technical and financial analysis that allowed observing the viability of the Project.